Construction of Criminal Policies for Handling Football Riots in the Kanjuruhan Tragedy - Astuti, Laras; Soponyono, Eko; Sularto, RB; Genovés, Manuel Beltrán (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2000)
Even though conflicts between supporters caused the majority of the riots, other factors were no less important. Specifically, those related to the organization of football matches that were not yet professional could not guarantee security or order. The incident at Kanjuruhan Stadium serves as a significant reminder that hosting football matches without prioritizing proper safety measures and collaborative procedures will undoubtedly fail to promote fair competition in line with the principles of organizing sporting events that uphold sportsmanship, fair play, and respect. This paper is compiled through normative research by prioritizing secondary data that focuses on statutory and case approach, which are collected and analyzed descriptively and qualitatively. The results shows that the legal construction used in carrying out security by the Police in the Kanjuruhan Tragedy refers to the Regulation of the Chief of Police of the Republic of Indonesia Number 1 of 2009 on the Use of Force in Police Action while after the Kanjuruhan Tragedy, the Police compiled a new legal construction, the Republic of Indonesia National Police Regulation Indonesia Number 10 of 2022 on Security for the Implementation of Sports Competitions which can be used specifically in securing the implementation of football in Indonesia